Management of biowaste for biofuel production (Case of Study: Iran) - Salimi, Erfaneh (Εθνικό Μετσοβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2014)
The size and growth of population significantly affects the demand for energy globally. Providing sufficient food, water and land for everyone on the planet as well as the environmental threats such as climate change and waste generation, and also declining fossil fuels sources are the other major challenges of current century in the face of rising population. The volume of energy consumption and waste generation varies from regions to regions or country to country due to many different factors such as the economy, climate, rate of urbanization, characteristics of industrialization, fuel & power prices, government conservation policies, and other factors. The economic development process has traditionally been accompanied by rapid population growth and also increases in energy demand, which, together with rising demand in both developed and developing countries. The greatest share of population growth belongs to the developing countries. Among developing countries, Iran has been selected as a case of study to investigate various aspects of bioenergy in particular bio-fuel production from the existing biomass resources especially bio-waste, in this regard SWOT analysis will take place for qualitative evaluation of present strengths, weaknesses, opportunities and threats about bio-fuel production from bio-waste, to address current environmental, social and economic issues which Iran is facing due to the country’s development process.